(untitled) (Research, Society and Development, 2023)
Variations in mortality and morbidity related to mental and behavioral disorders reflect a complex interaction between individual, social and health factors. Therefore, this study aims to determine the number of hospitalizations and the mortality rate caused by mental and behavioral disorders in the state of Pará between the years 2017 and 2022. To achieve this objective, a retrospective cohort study was carried out with data from DATASUS. The sample comprised all cases of emotional and behavioral disorders, registered in DATASUS and occurring in the State of Pará in the period from 2017 to 2022, with the population restricted to cases of hospitalization and death that occurred in the same period. The results demonstrate a gradual and constant increase in the number of hospitalizations over time. It was also found that 52% of hospitalizations occurred among male patients, aged between 20 and 29 years (28%), self-declared mixed race (79%). Regarding mortality, in 2017, the rate was 6%, indicating a low mortality rate related to mental and behavioral disorders in the state. However, there was a sharp increase in 2018, reaching 28%. In view of the results found, it is necessary to strengthen public mental health policies in the state of Pará, with an emphasis on prevention, promotion of mental health, access to specialized services, training of health professionals and raising awareness among the population about the importance of mental health care. mental health.